"Gut–brain axis": Review of the role of the probiotics in anxiety and depressive disorders. Issue 10 (10th September 2020) - Gambaro, Eleonora; Gramaglia, Carla; Baldon, Giulia; Chirico, Emilio; Martelli, Maria; Renolfi, Alessia; Zeppegno, Patrizia
Abstract: Background: Depressive disorders are the leading cause of disability worldwide and together with anxiety contribute to a very high burden of disease. Therefore, improving their treatment is a significant medical research target: The role of probiotics is a topic of great interest for the current research in this field. Objectives: To explore the current literature about the impact of probiotics on anxious and depressive symptoms. Methods: Scoping review following the PRISMA guidelines. Results: The selection process yielded 23 studies. Probiotics positively affected depressive symptomatology and anxiety symptoms according to 53.83% and 43.75% of the selected studies, respectively. Among the studies assessing inflammatory biomarkers, 58.31% found they were decreased after administration of probiotics. Conclusion: The results emerging from the existing literature about probiotic supplementation for depression treatment are encouraging, but further research is needed considering the shortage of clinical trials on this topic and the heterogeneity of the samples analyzed. Abstract : (a). Recently, the concept of "gut‐brain axis" has been of great interest for the research and the hypothesis that probiotic treatment could improve the symptomatology and the inflammatory status of the patients affected by depression has emerged. (b). Many trials, studying the effects of probiotic intake on depressive symptoms and inflammatory biomarkers status, were published and their results looks promising, even if only few studies included a population with a diagnosis of depression. 3. For this reason, other trials and reviews are needed to increase the knowledge in this branch of research.